BUMIPUTRA AUTHOR'S RESISTANCE TOWARD POLITICAL HEGEMONY AND CANONIZATION OF BALAI PUSTAKA IN THE NOVEL HIKAYAT KADIROEN AND STUDENT HIDJO - Sulistyo, Hary; Sartika, Endang (LITERA, 2020)
The ideological and aesthetic contestation of Balai Pustaka, forcing writer"Ÿs resistance particularly Bumiputra writers. The ideological contestation occurs because Balai Pustaka as the apparatus of the Colonial government suppress the resistance attitudes of the indigenous authors. The authors, who ideologically contradicted with the government, resisted the politics of literature through their works. This research is intended to reveal the canonization of Balai Pustaka which governs the aesthetic and ideological standards of literary works and the resistance of Bumiputra authors toward the hegemony of the Dutch East Indies. The method used in this research is descriptive qualitative approach by seeing the text as the representation of hegemony and resistance as well as linking textual and contextual issues to describe literary politics and the reflection of general politics. The objects of this research are the text and historical context represented in the novel Hikayat Kadiroen and Student Hidjo. The results show that Hikayat Kadiroen presents exemplary attitudes of fair leaders in solving peoples"Ÿ problems and representing the identity of Indonesian literature. Whereas Student Hidjo portrayed concern for the Indigenous people by criticisizing the political hegemony on racial basic. The resistance of Bumiputra authors was shown by raising resistance theme toward colonialism in the Dutch East Indies, as a form of resistance toward political hegemony and canonization of Balai Pustaka. Keywords: hegemony and resistance, Dutch East Indies, cultural identity. RESISTENSI PENGARANG BUMIPUTERA TERHADAP HEGEMONI POLITIK DAN KANONISASI BALAI PUSTAKA DALAM NOVEL HIKAYAT KADIROEN DAN STUDENT HIDJO Abstrak Kontestasi ideologis dan estetis Balai Pustaka, menghadirkan sikap-sikap perlawanan khususnya para penulis Bumiputra. Pertarungan ideologis terjadi karena Balai Pustaka sebagai apparatus pemerintah Kolonial, menekan sikap-sikap perlawanan pengarang Pribumi. Para pengarang yang secara ideologi berseberangan dengan pemerintah, melakukan resistensi atas politik kesusastraan melalui karya-karyanya. Tujuan penelitian ini mengungkapkan kanonisasi Balai Pustaka yang mengatur standar estetis dan idelogis karya sastra dan perlawanan kelompok Bumiputra terhadap hegemoni yang diterapkan di Hindia Belanda. Metode penelitian ini diawali dengan melihat teks sebagai representasi hegemoni dan resistensi dalam novel Hikayat Kadiroen dan Student Hidjo. Menghubungkan persoalan tekstual dan kontekstual untuk menjabarkan politik sastra dan cerminan politik general. Hasil penelitian menunjukan Hikayat Kadiroen menghadirkan sikap keteladanan pemimpin yang adil terhadap rakyat dalam menyeselaikan persoalan dan merepresentasikan identitas kultural kesusastraan Indonesia. Sedangkan Student Hidjo, menunjukkan sikap kepedulian terhadap Pribumi dengan kritik terhadap hegemoni politik atas dasar rasialis. Resistensi pengarang Bumiputra terhadap Balai Pustaka, ditunjukkan dengan mengangkat tema perlawanan terhadap kolonialisme di Hindia Belanda, sebagai bentuk resistensi terhadap hegemoni dan kanonisasi Balai Pustaka. Kata kunci: hegemoni dan resistensi, Hindia Belanda, identitas kultural.